A Modified Weber Number Capturing the Bouncing–Wetting Transition of Droplet Impact on Rough Surfaces. Issue 10 (2nd March 2023) - Bao, Yanyao; Wang, Zhongzheng; Shi, Zhang; Gan, Yixiang
Abstract: In this work, the effects of surface properties on bouncing–wetting transition of water droplet impacting rough surfaces in the Weber number ( We ) range from 18 to 221 are experimentally investigated. The correlation between impact outcomes and We is examined with an empirical function, and an impact outcome transition from bouncing to no bouncing is identified with the increase of We . The results suggest that a higher surface area ratio promotes the bouncing to no bouncing transition on sample surfaces used in this study. To quantify the effects of surface wetting area on the transitions of droplet impact regimes, a modified Weber number, We *, is proposed by taking the actual surface area into account. Results show that the regime transitions of droplet impact on samples of different surface area ratios can be unified by the We *. This study reveals the significance of actual surface area and the resultant adhesion force on the droplet impact dynamics on random rough surfaces. Abstract : Different preferences over modes of droplet spreading and bouncing behavior are observed. A modified Weber number considering a combined effect of inertial force, surface tension force, and adhesion force to capture the droplet bouncing–wetting transition behavior is further proposed. The results suggest that a higher surface area and root‐mean‐square roughness promote the transition from bouncing to wetting.